Operations Improvement to Design Work Policy: Priority Identification by Using QFDF - Rika Fatimah PL, Rika (The Indonesian Mathematical Society, 2012)
Abstract. This paper discussed the improvement action for operations in the organization. The improvement shall value of designing work policy to be better and more effective. The new approach is taken by considering family performance of the human resaource. Samples involved 1,213 respondents, who are married and have children, are selected from Peninsular Malaysia. Three dimensions that have been identified as important parameters for determininq the family performance are family relationship, family growth and family maintenance. A quality based approach, also taken under Operations Management. theori, is utilized to analyze the responses of respondent in determining the family performance. QFDF stands for Quality Function Deployment for Family is used to identify the priority action need to be taken to improve the operations in the organization. In addition, QFDF is appluied to match the quality dimensions in the concept of orqnnization to the dimensions under family life. The findings of QFDF are presented using House of Quality (HOQ) to project the family performance into quality of working in an organization.